Layered CNS Interface Framework for Civil–Military Airspace Integration: A PRISMA-Based Systematic Review of Airspace Security Effectiveness - Santoso, Budi; Supriyadi, Asep Adang; Surjaatmadja , Surachman; Taufik, Robby Mochammad; Sena, Afen (AGUSPATI Research Institute, 2026)
Airspace has evolved into a contested socio-technical domain in which civil aviation, military operations, and cyber infrastructures interact under increasing complexity yet remain structurally fragmented. Existing scholarship is dispersed across aviation safety, defense doctrine, and cybersecurity, limiting the development of integrative frameworks capable of explaining system-level security outcomes. While systems-of-systems (SoS) research predominantly emphasizes technical interoperability, the role of governance in structuring cross-domain integration remains insufficiently theorized.This study addresses this gap through a PRISMA-based Systematic Literature Review (SLR) of 35 high-relevance sources indexed in Scopus, Web of Science, and ScienceDirect. Adopting a SoS perspective, it develops the Layered CNS Interface Framework (LCIF) as a governance-driven, multi-layer integration architecture linking policy, operational, technological, and cyber dimensions.The synthesis suggests that airspace security effectiveness is shaped by three interdependent constructs—integration quality, interoperability, and adaptive capacity—within which civil–military air traffic management operates as a mediating mechanism translating structural integration into coordinated operational outcomes. These relationships are theoretically derived from cross-domain synthesis rather than empirically established.The study contributes by extending SoS theory into the domain of security governance and by reconceptualizing interoperability as a multi-dimensional construct encompassing technical, institutional, and decision-making alignment. The LCIF model provides a theoretically grounded and empirically testable foundation, enabling future examination of multi-layer causal relationships through Structural Equation Modelling (SEM) in complex airspace systems.